Thermal Influence of CNT on the Polyamide 12 Nanocomposite for Selective Laser Sintering - Bai, Jiaming (2015)
The thermal influence of carbon nanotubes (CNTs) on the PA12 in the laser sintering process was assessed by physical experiments and a three dimensional simulation model. It appears that, by adding the CNTs into the PA12 matrix, the thermal conductivity increased. A double ellipsoidal heat flux model was applied to input a three dimensional, continuous moving, volumetric laser heat source. The predicted three dimensional temperature distributions suggested that the laser heat was conducted wider and deeper in the PA12-CNT sample than PA12. Greater heat conduction can reduce the interspace between two successive layers, and result in the increase of the parts’ density and properties.